Virtual Account, Islamic Boarding School Innovation in the Era of Disruption in Providing the Best Services Focused on Customer Satisfaction - Muhammad Husain; Ainur Rofiq; Ali Wafa; Siti Aminah; Imamatul Qudsiyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The aim of this research is to analyze how the Darussalam Blokagung Islamic boarding school innovates in providing the best service for customer satisfaction. This research uses qualitative methods, this research focuses on one analysis, namely the services provided by the Darussalam Blokagung Islamic boarding school in providing the best service through the students' virtual accounts. Data collection techniques include in-depth interviews, direct observation, documentation and focus group discussions. The validity of the data in this research uses data triangulation. The data analysis technique uses an interactive model, starting from the stages of data reduction, data presentation and continuing with drawing conclusions. The results of this research show that the Darussalam Blokagung Islamic boarding school has provided the best service through the virtual account method, with the implementation of this financial management program, especially during the payment process, it can provide ease of transactions, ease of monitoring students' financial circulation, and services with this program to provide a sense of satisfaction to all parties. who is served.